A database of life history parameters for Pacific coral reef fish - Anela K. Akiona; Brian J. Zgliczynski; Marisa M. Agarwal; Beverly J. French; Nathaniel Hanna Holloway; Katie A. Lubarsky; McClaran E. Shirley; Christopher J. Sullivan; Stuart A. Sandin (Scientific Data)
Abstract Length-weight parameters assist in the estimation of a fish’s biomass based upon assessment of length, providing value to many scientific and management applications. Some fish species have many sets of parameters published, while those less commonly studied may have no available information, making it challenging to decide which values to use. To address this, we present a database of quality-controlled length-weight parameters for 1,308 Pacific coral reef fish species from 87 families. The species included are commonly observed in visual censuses of shallow (10 m depth) forereef habitats of the central Pacific. These data were collated from the literature, and were selected based on study sample size, representation of the species’ total length range, and data confidence. The most speciose families, wrasses (Labridae) and damselfishes (Pomacentridae), were most common in our database, though a large proportion of these species remain data-poor. In total, this database serves as a valuable tool for the academic community as well as for partners and managers desiring to learn more about coral reef fish assemblages.